2019
DOI: 10.1002/mds.27918
|View full text |Cite
|
Sign up to set email alerts
|

Swimming is Compromised in Parkinson's Disease Patients

Abstract: Background A recent survey reported a high risk of drowning in Parkinson's disease (PD) patients. This study intended to assess PD patients’ swimming ability and explore the disease‐related characteristics that may affect this. Methods A cross‐sectional study was conducted in idiopathic PD patients. The assessment included swimming in 2 different styles and the evaluation of isolated technical gestures. The primary outcome was the frequency of patients who were able to swim. Limb coordination, blockage episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…With respect to grouped medical conditions, diseases of the nervous system [ 7 , 11 , 19 , 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and mental and behavioural conditions [ 7 , 37 , 42 , 43 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to grouped medical conditions, diseases of the nervous system [ 7 , 11 , 19 , 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and mental and behavioural conditions [ 7 , 37 , 42 , 43 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…Almost half (49.1%) of all people in Portugal and the United Kingdom (UK) surveyed with Parkinson’s Disease reported having experienced a non-fatal drowning [ 48 ]. Drowning deaths of people with dementia who die after going missing or wandering span from 11.3% to 42.1% [ 36 , 51 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…If, after accessing webpage information, people with PD are not aware that there are potential harmful side effects associated with aquatic physiotherapy or alternatively have not been screened by a medical professional to ensure they are suitable candidates for this treatment modality, they may make an uninformed choice that could lead to harm or injury. Considering people with PD have impaired swimming ability and are unable to maintain a horizontal position in the water or float with ease [ 16 , 17 ], it is a recommendation from this study that all webpages list potential contraindications to aquatic physiotherapy and also direct people with PD to seek advice from their medical practitioner or physiotherapist to determine whether aquatic physiotherapy is the best therapy choice for that individual.…”
Section: Discussionmentioning
confidence: 99%
“…The aquatic environment can however cause orthostatic hypotension or shortness of breath in people with PD, a vulnerable population. Previous literature has shown that swimming is compromised in people with PD [ 16 ] and that people with PD have difficulty maintaining a horizontal position in water due to bradykinesia and impaired coordination [ 17 ]. It is, therefore important that information regarding the therapeutic environment such as pool depth, water temperature, and staff supervision are fully described and that patients or consumers are aware of any possible contraindications to minimise possible adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Two years after my experience another article described swimming problems in many Parkinson's patients, with or without DBS. Using underwater videos the authors showed that the problem was a lack of coordination between the upper limbs and lower limbs and an inability to keep the body parallel to the water (Neves et al, 2020). The experience led me to have a much greater appreciation of the complexity of normal body movements that we take for granted.…”
Section: Freezing and Drowningmentioning
confidence: 99%